Cadmium Accumulation and Tolerance of Talinum paniculatum Callus Culture - Miranda Gardha Viorenta; Ratih Restiani; Dwi Aditiyarini (UIN Sunan Gunung Djati Bandung, 2025)
The increasing use of inorganic fertilizers is one of the main factors contributing to increased Cadmium (Cd) pollution in the environment. Phytoremediation is one of the strategies that can be used to address the problem of Cd pollution in the environment. The selection of Cadmium-tolerant plants can be conducted using an in vitro culture. Talinum paniculatum as an ornamental plant is potentially used as a phytoremediation agent, but limited information is available regarding its accumulation ability and tolerance to cadmium stress. Therefore, this study aims to determine the accumulation ability and tolerance of T. paniculatum callus to cadmium at various concentrations. This study used a completely randomized design (CRD) with six replications of Cd concentration treatment (0, 5, 10, and 20 ppm). Accumulation and tolerance of callus to Cd were assessed based on callus biomass, callus color, tolerance index, heavy metal concentration in callus and media, and Bioconcentration Factor value. An increase in Cd concentration showed a change in callus color from yellowish green to blackish. In addition, there was no significant difference in dry weight (0.078-0.086 g) and tolerance index (102.631%-113.158%) of callus. However, increasing Cd concentration showed significant differences in callus Cd accumulation from media (5-20 ppm) and Bioconcentration Factor (BCF) ratio (1.282-5.701), indicating the ability of T. paniculatum as an accumulator plant. This study's results support phytoremediation efforts against heavy metal pollution, including cadmium.